Faktor- Faktor Penyebab Terjadinya Pernikahan Dini Yang Terjadi Pada Kalangan Remaja Muda Di Desa Nangahale Kecamatan Talibura Kabupaten Sikka - Ririn Aryuni M.Lapi; Widya Astuti (Hikamatzu | Journal of Multidisciplinary, 2024)
Marriage in the perspective of Law of the Republic of Indonesia no. 1 of 1974 article 7 regulates the minimum age limit for marriage where marriage is only permitted if the man has reached the age of 19 years and the woman has reached the age of 16 years. This research aims to determine the factors that influence the occurrence of early marriage among teenagers in Nangahale Village, Talibura District. The research method used is descriptive qualitative. The data sources used use primary and secondary data. Primary data sources come from religious figures, community leaders, and parents. Secondary data sources were obtained from documents in the form of books, journals, and mass media. Data collection techniques are observation, interviews, and documentation. The data analysis technique used is that data is collected through interviews and observations, after that it is sorted and grouped based on research objectives, then verification and concluding. The research results relate to the factors that cause early marriage among teenagers in Nangahale Village, namely pregnancy out of wedlock, lack of education, economic factors, development of science and technology, and promiscuity